Constructive and functional particularities of 3D printers with applications in the food industry. Issue 1 (December 2020) - Besnea, D; Avram, M; Cananau, S; Moraru, E; Spanu, A; Constantin, V; Panait, I C
Abstract: The paper presents the construction and operation of a 3D printer that uses the principle of food raw material extrusion with possible applications in the food industry. The emergence of these additive technologies has led to the obtaining of complex customized three-dimensional products starting from a 3D CAD model. Among the advantages of this technology with applications in the food industry can be listed: obtaining personalized food products with innovative forms especially in the confectionery and pastry area; obtaining food products that have in the component known raw materials (allergies, intolerance), forms, colour, strictly controlled nutritional value; the possibility of integrating this technology in long-term space missions by creating foods of different shapes and compositions. Also, older people can be helped to deal with the problems of chewing and swallowing. The disadvantages of 3D printing technology with applications in the food industry are related to food safety, because strict hygiene conditions and working temperature control must be ensured. Also, the future development of this technology can lead to the saving of large quantities of food raw materials.